Periprocedural Plasma Fibrinogen level and Clinical Outcome of Coronary Stent Implantation - Mohammad Samsuzzaman, Sheikh; Khaled, Md Fakhrul Islam; Ahmed, Sayed Mainuddin; Md Al Amin, -; Rashed, Rakibul; Abedin, Md Zainal; Rahman, Hossain Muhammad Mustafijur; Bari, Mohammad Anwarul; Islam, Md Azharul; Hoque, Md Harisul; et al. (University Heart Journal, 2021)
Coronary artery disease (CAD) is the leading cause of mortality and morbidity both in developed and developing countries. Percutaneous recanalization of occluded coronary artery is one of the treatment options and reinfarction and restenosis negatively affect the outcome following procedure. Although various factors including fibrinogen are suspected as risk factors for this but its role in adverse outcome after stent implantation is controversial. The aim of this study was to determine the impact & relation of periprocedural fibrinogen level on outcome after coronary stent implantation. This prospective study was conducted in the Department of Cardiology, University Cardiac Centre, Bangabandhu Sheikh Mujib Medical University (BSMMU), Hospital, Dhaka over a period of one year between July 2016 to June 2017. Total 53 patients of chronic stable angina (CSA) undergoing elective PTCA followed by stenting were included in this study as per inclusion and exclusion criteria. Plasma fibrinogen level was measured by collecting venous blood samples at three timed points in relation to stenting – 24 h before, 24 h after and 72 h after stenting. Recurrence of angina, myocardial infarction, repeat revascularization (either PCI or Cardiac surgery), and death were considered as adverse outcome during follow up at 1, 3 and 6 months after intervention. During the 6 months follow up period 1 (one) patient developed UA (at 1 month), 2 developed MI (1 at 3 month and 1 at 6 month) and 2 died (1 at 3 month and 1 at 6 month). Patients were grouped on the basis of four outcomes: favorable outcome (those who did not develop any of the four outcomes) and unfavorable or adverse outcome (those who developed any of the four outcomes). The mean age of study population was 53.92 years and 39 (73.6%) were male. Regarding cardiovascular risk factors, 43.4% patients had diabetes mellitus, 88.6% had dyslipidaemia, 56.6% were non-smokers. Baseline plasma fibrinogen level were significantly higher in patients who developed complications following PCI than those who did not develop the complications (394.4 ± 16.0 Vs 271.5 ± 21.8 mg/dl) & remained high after 24 hours and 72 hours following PCI (p < 0.001). Angiographic profiles of the study population reveals 84.9% LAD, 16.9% RCA & 15% LCX involvement but there was no association of post-PCI adverse outcomes with vessels involved, number of stents deployed and types of stents used (p > 0.05). Study showed that the risk of developing unfavorable outcome following PCI in patients with pre-PCI & post-PCI high serum fibrinogen was estimated to be 5.7 times & 12 times higher than those who have had serum fibrinogen lower than 350 mg/ dl respectively (p = 0.023 & 0.025 respectively). High serum fibrinogen can therefore be used as a marker for predicting adverse outcome following PCI. University Heart Journal Vol. 17, No. 2, Jul 2021; 122-127